Very compact differential transformer-type bandpass filter with mixed coupled topology using integrated passive device technology. Issue 12 (December 2015) - Li, Yang; Wang, Cong; Yao, Zhao; Kim, Nam-Young
Abstract: This paper presents a very compact differential transformer-type bandpass filter based on mixed coupled resonators that are developed using integrated passive device technology on a GaAs substrate. The center frequency of the proposed BPF is 900 MHz with a 3-dB fractional bandwidth of 85%, which is applicable to the long-term evolution application frequency range for band 8; the overall size of the filter is notably small compared with other studies and is only 7.5×10 −3 λ 0 ×7.5×10 −3 λ 0 . The implemented differential type transformer offers a high coupling effect to ensure that the final device has excellent RF performance. Moreover, the proposed structure greatly reduces the size and introduces two transmission zeros near the passband edge in the stopband, which results in a high level of selectivity and harmonic suppression. Meanwhile, it is possible to control the rejection level by adjusting the capacitor electrode sizes, which provides greater design flexibility. Finally, experimental verification demonstrates very good agreement between the modeled and measured results, thereby validating the correctness of the proposed filter design based on the integrated passive device process.